World Climate Research Programme Special Workshop on Climatic Effects of Ozone Depletion in the Southern Hemisphere - Canziani, Pablo Osvaldo; Oneill, Alan; Schofield, R.; Raphael, M.; Marshall,G. J.; Redaelli, G. (Bulletin of the American Meteorological Society)
A World Climate Research Programme (WCRP) Special Workshop titled the “Climatic effects of ozone depletion in the Southern Hemisphere: Assessing the evidence and identifying gaps in the current knowledge” focused on the current understanding of Southern Hemisphere (SH) ozone depletion, in particular high-latitude ozone depletion, with regards to its impacts on hemispheric climate and its role relative to greenhouse gas (GHG)–induced climate changes. The 2010 United Nations Environment Programme (UNEP)/World Meteorological Organization (WMO) Scientific Assessment of Ozone Depletion, and research published since, provided the starting point for discussion. The workshop was supported by WCRP, the National Science Foundation (NSF; United States), the National Aeronautics and Space Administration (NASA; United States), Agencia Nacional de Promoción Científica y Técnica (Argentina), and the Pontificia Universidad Católica Argentina (Argentina). Fil: Canziani, Pablo Osvaldo. Pontificia Universidad Católica Argentina Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Oneill, Alan. National Centre For Earth Observations; Reino Unido Fil: Schofield, R. University of Melbourne; Australia Fil: Raphael, M. University of California at Los Angeles; Estados Unidos Fil: Marshall,G. J. British Antarctic Survey; Reino Unido Fil: Redaelli, G. Universita degli Studi dell'Aquila; Italia